Back Cover Image. Issue 12 (19th December 2022) - Wang, Rui; Li, Xinyu; Qin, Zheng; Wang, Lintao; Lin, Zhimin; Wang, Xuan; Tian, Hua; Shu, Gequn
Abstract : COVER CAPTION: The Back cover image is based on the Original Article Dynamic response and emergency measures under failure conditions of sCO2 Brayton cycle by Rui Wang et al., https://doi.org/10.1002/ese3.1300 .